Wetter und Architektur. Bauen für die Zukunft. - (:unkn) unknown (good!movies, 2014)
An outstanding example of new architecture: the Frankfurt city planning programme between 1925 and 1930. Appointed head of the Frankfurt municipal planning and building control office in 1925, Ernst May asembled a team of young architects, planners and designers. With the extensive need for modern living design but also a rational cost-effective building approach through standardised ground plans and building components, the use of local companies and the unemployed, THE NEW FRANKFURT distinguished itself as the most innovative major project of new architecture in the 1920's. In addition to the original film by Dr. Paul Wolff from the 1920's, this edition presents the in-depth WDR documentary.
The new Frankfurt. Films by Paul Wolff, Jonas Geist and Joachim Krausse.
Keywords: Bebauung; Witterung; Klima; Naturkatastrophe; Bauweise; Architektur; Klimawandel; Anpassung